Characterization of common bean (Phaseolus vulgaris L.) germplasm for morphological and seed nutrient traits from Western Himalayas. Issue 2 (29th March 2021) - Jan, Sofora; Rather, Irshad Ahmad; Sofi, Parvaze Ahmad; Wani, Mohd Altaf; Sheikh, Farooq Ahmad; Bhat, Mohammad Ashraf; Mir, Reyazul Rouf
Abstract: Common bean ( Phaseolus vulgaris L.) is considered as one of the principle grain legume crops grown in Western Himalayas of Jammu and Kashmir, India. This region holds great diversity of common bean germplasm. The purpose of present study was to characterize 109 common bean genotypes collected from different hotspots for morphological traits—plant growth (growth habit, growth type, and twinning habit); leaf (color, size, and shape); flower (color, stripping on outer petal); pod (shape in relation to suture, shape of cross‐section, shape of distal part, and stringiness), seed (color and shape) traits, and quantitative morphological traits (seed weight, length, and breadth). The preliminary analysis of trait data showed wide variation for different morphological traits. Furthermore, diverse 60 genotypes were selected out of 109 genotypes and were evaluated for seed micronutrients (Fe, Zn, and Cu) and seed macronutrients (K, Ca, P, and Mg). The analysis of seed micronutrient and macronutrient data indicated substantial variation for these minerals in the germplasm. Seed Mg, P, K, and Ca concentrations varied from 1, 220.5 to 2, 737.5 ppm, 1, 980–4, 050 ppm, 8, 344.5–14, 794 ppm, and 300–5, 350 ppm, respectively. Similarly, seed micronutrients Fe, Zn, and Cu concentrations ranged from 80.5–180.6 ppm, 14.64–104.08 ppm, and 0.9–13.4 ppm, respectively. The evaluation for seed micronutrient and macronutrient led to the identification of candidate genotypes possessing high seed micronutrient and macronutrient. The candidate genotypes identified during the present study will prove useful in common bean breeding programs as donor genotypes, in development of useful genetic resources and in gene discovery programs through functional genomics and transcriptomics.